2006
DOI: 10.1038/sj.hdy.6800851
|View full text |Cite
|
Sign up to set email alerts
|

Among- and within-population variation in outcrossing rate of a mixed-mating freshwater snail

Abstract: Mixed-mating animals self-fertilize a proportion of their offspring. Outcrossing rate may covary with the ecological and historical factors affecting the population. Theory predicts that outcrossing is favored when inbreeding depression is high and when individual heterozygosity is important. Self-fertilization is predicted to be favored when costs of male function, or mate finding are high, for example, when empty patches are colonized by few individuals. In this study, we assessed primary (after hatching) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This indirect approach also allows the magnitude of inbreeding depression to be conveniently compared among populations. Hence, in several evolutionary and ecological studies, levels of late‐stage inbreeding depression have been estimated using this method (Keller & Waller 2002; Hodgins & Barrett 2006; Jokela et al . 2006; Edmands 2007; Kubota et al .…”
Section: Introductionmentioning
confidence: 99%
“…This indirect approach also allows the magnitude of inbreeding depression to be conveniently compared among populations. Hence, in several evolutionary and ecological studies, levels of late‐stage inbreeding depression have been estimated using this method (Keller & Waller 2002; Hodgins & Barrett 2006; Jokela et al . 2006; Edmands 2007; Kubota et al .…”
Section: Introductionmentioning
confidence: 99%
“…Selfing is predicted to predominate when there are high costs for the male function or for mate searching, even though selfing may lead to a loss of heterozygosity (e.g. Jarne and Städler 1995;Jokela et al 2006). Overall, the higher efficiency of gene transmission through selfing compared to outcrossing is thought to be counterbalanced by inbreeding depression (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…producing selfed or outcrossed offspring (e.g. Henry et al 2005;Jokela et al 2006). A few studies showed that individuals can also perform mixed fertilisation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hatching success was determined after 2 weeks (Jokela et al 2006) by recording hatched snails, undeveloped eggs, and developed but not hatched embryos in the egg clutch using a stereomicroscope and analysed as mean hatched eggs (%) per treatment. To quantify hatching success for B. tentaculata, eight egg-clutches per replicate and treatment was photographed after 3 weeks (Cather and Verdonk 1974) recording undeveloped eggs and developed but not hatched embryos by comparing the images before and after the 2 weeks.…”
Section: Methodsmentioning
confidence: 99%